Healey, Heather. Presumed Drowned. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Heather Healey, a Grade 8 student at Villanova Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Heather writes, "I got my story on the internet. I chose this story because it seemed interesting and it is a Newfoundland story. It's a story about 77 men who went out on the ice to kill seals and there was a two day storm, and the men couldn't get back to their boat."